Introducing a static receptor to compete with a dynamic combinatorial library in template binding. Issue 42 (30th September 2015) - Ulatowski, Filip; Lichosyt, Dawid; Jurczak, Janusz
Abstract : Association constants can be obtained from HPLC analysis of a system comprising a dynamic combinatorial library and a static host. Abstract : We show herein that establishing a competition between a static receptor and components of dynamic combinatorial libraries to bind an appropriately selected template can be used to determine association constants by HPLC analysis after freezing of the equilibrium.